The efficacy and safety of stepwise oral food challenge in children with hen’s egg allergy - Mika Ogata; Jun Kido; Takanobu Yoshida; Natsuko Nishi; Sachiko Shimomura; Nami Hirai; Tomoyuki Mizukami; Masaaki Yanai; Kimitoshi Nakamura (Allergy, Asthma & Clinical Immunology, 2024)
Abstract Background Oral food challenge (OFC) is the gold standard for diagnosing food allergies (FAs) but carries the risk of anaphylactic reaction. Stepwise OFC, starting with a low dose of allergen and progressing to medium and full doses, is effective in determining a tolerable dose. We retrospectively evaluated the results of a stepwise OFC for hen’s egg (HE) to demonstrate its safety and efficacy. We discuss whether early low-dose administration of HE induces early immune tolerance in HE allergy. Methods We included 2,058 children (median, 2.6 years) who underwent HE-OFC between 2017 and 2021 at two institutes in Japan. The target challenge dose of OFC was classified as low (less than 1/8 of a cooked egg), medium (1/8 or more but less than 1/2), or full (1/2 or more). If the low-dose OFC was negative, subjects were allowed to consume the same dose of HE and underwent medium-dose OFC within 12 months. Even if positive, individuals were recommended to consume previously-tolerated amounts of HE and repeat OFC at the same dose within 12 months. We evaluated the correlation between their OFC results and response. Results A total of 526 (25.6%) children presented positive reactions. There were no cases of anaphylactic shock. Higher serum egg white (EW)- (P < 0.001) and ovomucoid (OVM)- specific IgE (P < 0.001) (sIgE) levels were associated with positive OFC. The low-dose OFC group had more positive reactions (P < 0.001), younger children (P < 0.001), higher EW-sIgE (P < 0.001) and OVM-sIgE (P < 0.001), and more histories of anaphylaxis (P = 0.014). OFC-positive children were younger than OFC-negative children, particularly in low-dose OFC (P = 0.010). OFC results between complete and partial elimination of HE groups across all EW- or OVM-sIgE classes were similar (P > 0.05). Conclusions Stepwise OFC is safe and effective in diagnosing HE allergy and facilitates the earlier introduction of HE in children. This study suggests the limited potential of early consumption of lower doses of HE to induce earlier immune tolerance, such that other strategies to induce earlier tolerance in infants with HE allergy should be considered.